Feeding behavior is the main driver for microparticle intake in mangrove crabs. Issue 1 (7th January 2020) - Not, Christelle; Lui, Cheuk Yan Iris; Cannicci, Stefano
Abstract: As marine plastic debris is primarily sourced from terrestrial input, coastal environments are particularly affected by deposition. Because of their pneumatophores, mangroves have been recognized for their importance in confining plastic waste. Crabs are a dominant component of the mangrove ecosystem and play a critical role in maintaining healthy and resilient mangrove forests. Therefore, the presence of debris fragmented from waste, in their habitat is a potential threat. However, the potential ingestion of microplastic pieces by mangrove crabs has not yet been investigated. Here, we quantified microparticles found in the cardiac stomachs and gill chambers of four species of crabs. All specimens collected had anthropogenic microparticles present either via their digestive or respiratory systems. We observed significant variability in the abundance and types of anthropogenic microparticles across sites and species. Interspecific differences appear to be explained by their particular feeding habits, with less selective species ingesting more particles.